Rola Śląskiego Oddziału Polskiego Towarzystwa Historycznego (1929–1939) w popularyzacji wiedzy o przeszłości Śląska (PDF 7,81 MB) (Książnica Śląska, 2025)
The Silesian Branch of the Polish Historical Society was foundedin 1929 on the initiative of the Silesian Voivode Michał Grażyński,historian Roman Lutman, and head of the Department of Public Education in Katowice, Ludwik Ręgorowicz. Their main objective wasto support Silesian historical research and promote knowledge aboutthe history of Silesia. This article presents the process of establishingthe Silesian branch of society and its main activities, such as lectures,research work, and didactics. Additionally, it discusses the branch’scollaboration with other scientific and cultural institutions in UpperSilesia during the interwar period, including the Society of Friendsof Science in Silesia and the Institute of Silesia. The author also mentions the participation of the members in the Universal Congressof Polish Historians.